A discrete choice experiment to investigate patient preferences for HIV testing programs in Bogotá, Colombia (2019)
Background: To assess patients’ preferences for HIV testing in Colombia. Methods: A discrete choice experiment was used to assess preferences of patients diagnosed with HIV, for HIV testing in two HIV clinics in Bogotá, Colombia. Patients were asked to choose repeatedly between two hypothetical HIV testing options that varied with respect to five attributes: distance to testing site, confidentiality, testing days, sample collection method, and the services if HIV positive. A random parameter model was used to analyze the data. Results: A total of 249 questionnaires were eligible for data analysis. Respondents showed a preference for testing on weekdays, nobody being aware, a sample taken from the arm, and receiving medications through a referral. The respondents showed a high negative preference for many people being aware, followed by testing during the weekend and home testing. Subgroup analyses by gender and prior testing history did not reveal significant differences. Conclusion: This study suggests that patients’ preferences for HIV testing focused especially on confidentiality, availability during weekdays, and using a sample from the arm. This information could be useful to improve uptake of HIV testing in Bogotá, Colombia. © 2018, © 2018 Informa UK Limited, trading as Taylor and Francis Group.